PENGARUH LIMA DIMENSI KEPRIBADIAN TERHADAP MODAL SOSIAL (Studi Kasus di SMA se Kecamatan Kendal) - 11.52.02.0095, Nur Yulfiati (Jurnal Mahasiswa Pasca Sarjana, 2013)
Social capital is very useful for teachers because it will support the work process . Teachers who have social capital is both easy access to the wider resources so as to improve the quality , relevance , and timeliness of the information necessary for teachers to support their work.Entire study population Teachers in public and private high school in Kendal district , as many as 133 teachers . The research sample of 100 teachers with proportional random sampling technique . Data analysis and hypothesis testing using multiple regression with SPSS 16.0 for windows release . Hypothesis 1 , beta .390 on the sign . 0.000 < 0.05 , personality neoriticism positive and significant effect on dimensional structural dimension , hypothesis 2 , beta .532 on the sign . 0.000 < 0.05 , Extraversion personality positive and significant effect on the structural dimension , hypothesis 3 , beta - .312 to sign . 0.003 < 0.05 , personality Openness to new experience and a significant negative not effect on structural . Hypothesis 4 , Beta .206 to .165 sign > 0.05 , Agreeableness personality does not affect the structural dimension , hypothesis 5 Beta .183 to .041 sign < 0.05 counscientiousness positive and significant effect on the dimensions , Hypothesis 6 , beta .218 sign . 0.018 < 0.05 neoriticism positive and significant effect on the relational dimension , hypothesis 7 beta .703 sign . 0.000 < 0.05 Extraversion positive and significant effect on relational . Hypothesis 8 beta - .171 sign . 0.049 < 0.05 Openness to new experience and a significant negative not effect on relational . Hypothesis 9 .133 beta sign . .285 > 0.05 Agreeableness had no influence on the relational . Hypothesis 10 beta sign .117 .119 > 0.05 counscientiousness no effect and no significant effect on relational . Hypothesis 11 beta - sign .855 0.029 < 0.05 neoriticism negative and significant effect on cognitive , hypothesis 12 beta sign .725 0.001 < 0.05 Extraversion positive and significant effect on cognitive , sign beta.047 hypothesis 13 0.898 > 0.05 openness to new experience had no effect on cognitive capital . Hypothesis 14 beta sign .812 .127 > 0.05 Agreeableness had no effect on cognitive capital , hypothesis 15 beta sign .239 .455 > 0.05 counscientiousness no influence on the cognitive dimension of social capital. Keywords: Five Dimensions of Personality, social capital